First record of the American cestode Proteocephalus ambloplitis (Leidy, 1887) (Proteocephalidae) in Europe - Kvach, Y; Seifertová, M; Carassou, L; Ondračková, M (Journal of helminthology, 2020)
Here, we report the first record of pleroceroids of the Nearctic tapeworm Proteocephalus ambloplitis (Leidy, 1887) in European fresh waters. The plerocercoids were found encapsulated in the internal organs of the invasive pumpkinseed Lepomis gibbosus (Linnaeus, 1758) in a pond in Bègles Plage, Bordeaux, France. This parasite species was not observed in L. gibbosus collected from two nearby localities, Bordeaux Lac and a pond in the Parc de Fontaudin. Species identification was confirmed using molecular data and morphological characteristics.
Keywords: Cestoda; non-native species; Perciformes; parasites; Ponds; Fish Diseases; France; cestodózy; Invasive fish; Francie; sladká voda; Fresh Water; Bègles Plage; rybníky; Animals; plerocercoids; dějiny 19. století; zvířata; nemoci ryb; History, 19th Century; Cestode Infections